ECONOMY OF CENTRAL ASIAN COUNTRIES - E. Tlessova, E.; Khoich, A.; Kuras, N. (Academic Journal of Physical and Chemical Sciences, 2018)
The modern world is characterized by instability, a change in balance sheets and a change in the system of international relations. After the collapse of the Soviet Union, Central Asia was at the center of attention of various external forces. The region was at the intersection of interests of both regional and global players. For the world economy, the Central Asian region is interesting, first of all, as a source of raw materials. Oil, gas, coal and metals are currently the most popular exported goods, in turn, agricultural products also provide dynamic growth for last years. During the quarter century independence Central Asian countries has developed in different ways and trajectories. One has made big economic impulse and other one has slow down and face big crises. But all the time period Central Asian countries have common priorities in economy and development. Because those countries are connected not only by geographically, at the same time culturally, mentally even in some cases economic political issues. Article is about economic development and tendencies of Central Asian states as whole and separately. Author gives from general to detailed analyses of GDP growth and its structure. On the other hand analyzes investment climate and investment attractiveness of countries. Which explains countries’ and region’s current economic situation